Predictors of Professional Identity in Psychology Students: a Path Analysis Study - Cuadra-Martínez, David J. (2019)
The aim of this study was to determine the relationship between professional identity, university student identity, academic self-efficacy, professional self-efficacy, credits taken and difficulty perceived in the career, in traditional and non-traditional psychology students. We used a cross-sectional design and a non-probabilistic sample of 136 psychology students from a public university in the north of Chile. Four scales and a sociodemographic survey were used. Descriptive statistics, Pearson correlation analysis, analysis of variance (ANOVA) and path analysis were performed. Results showed significant differences in the academic and professional self-efficacy grouped into traditional and non-traditional students and a model that predicts professional identity based on the variables of university student identity, academic self-efficacy, professional self-efficacy, credits taken and perceived difficulty in the career (R2= .24). Outcomes are discussed according to the existing literature.